Child interpreters - a South African case study - Louw, Gwendoline Susarah (My University, 2016)
The present study looks at the use of child interpreters in a South African context and its potential far-reaching, negative effects. Reference is made to studies conducted in other countries, with the aim of determining potentially similar findings locally. Focus groups and one-on-one interviews with service providers in contact with current child interpreters, as well as former child interpreters are conducted to establish their respective experiences with the phenomenon. Furthermore, questionnaires were also used as a data collection tool for subjects unable to attend interviews. The study employs a qualitative approach, with the use of a relatively small, but sufficient sample size. On the basis of the findings, the present report presents conclusions regarding the motives for the perpetuation of the practice of child interpreting, and it furthermore presents possible measures or regulations that need to be designed and implemented to protect the rights of the child interpreter.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Interpreting. Cape Town 2016.
Keywords: Translators--South Africa